2017
DOI: 10.1016/j.comppsych.2017.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the interpersonal model of loss of control eating in the laboratory

Abstract: Background The interpersonal model of loss of control (LOC) eating proposes that interpersonal problems lead to negative affect, which in turn contributes to the onset and/or persistence of LOC eating. Despite preliminary support, there are no data examining the construct validity of the interpersonal model of LOC eating using temporally sensitive reports of social stress, distinct negative affective states, and laboratory energy intake. Method 117 healthy adolescent girls (BMI: 75th–97th %ile) were recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 78 publications
1
22
1
Order By: Relevance
“…A secondary analysis of data from girls ages 12 to 17 years with BMI between the 75th–97th percentile and reports of at least one episode of LOC‐eating within the past month (http://clinicaltrials.gov ID: NCT00680979) was conducted. Inclusion/exclusion criteria have been described (Tanofsky‐Kraff et al, ), and other baseline data from this trial have been published (Glasofer et al, ; Jaramillo et al, ; Ranzenhofer et al, ; Shank et al, ) focusing on self‐efficacy, family functioning, and state NA in relation to laboratory eating patterns. Data were collected from participants before initiating a prevention program.…”
Section: Methodsmentioning
confidence: 99%
“…A secondary analysis of data from girls ages 12 to 17 years with BMI between the 75th–97th percentile and reports of at least one episode of LOC‐eating within the past month (http://clinicaltrials.gov ID: NCT00680979) was conducted. Inclusion/exclusion criteria have been described (Tanofsky‐Kraff et al, ), and other baseline data from this trial have been published (Glasofer et al, ; Jaramillo et al, ; Ranzenhofer et al, ; Shank et al, ) focusing on self‐efficacy, family functioning, and state NA in relation to laboratory eating patterns. Data were collected from participants before initiating a prevention program.…”
Section: Methodsmentioning
confidence: 99%
“…Lower social competence has been linked with obesity development and treatment studies suggest social skills development and improved social interaction may be particularly helpful for children with adjustment and anxiety issues in weight management [89, 90]. Social connectedness and interpersonal communication skills should be effective for the prevention and treatment of disordered eating as well, as social stress has been identified as a trigger for binge eating [91] and therapies designed to improve interpersonal relationships with peers have been demonstrated as effective for reduction of disordered eating in adolescents [92]. …”
Section: Fbt Treatment Componentsmentioning
confidence: 99%
“…LOC eating is associated with more anxiety symptoms in youth (Glasofer, et al, 2007; Goossens, et al, 2009; Morgan, et al, 2002; Shomaker, et al, 2010). Further, at least one study has shown that anxiety is the most salient mood state among youth with LOC eating (Shank, et al, 2017). Additionally, another study found that anxiety, but not depression, was associated with LOC eating in youth with overweight (Goossens, et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, socio-emotional neural circuits that commonly distinguish youth with anxiety from healthy controls may be relevant for youth who report LOC eating. Girls with overweight or obesity with reported LOC eating showed less activity in the ventromedial prefrontal cortex compared to girls without LOC eating (Shank, et al, 2017). Furthermore, a relationship between fusiform face activation and greater energy intake after exposure to peer rejection was observed only among those with LOC eating (Jarcho, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation